2015
DOI: 10.2298/bah1504515b
|View full text |Cite
|
Sign up to set email alerts
|

Tick fauna of the autochthonous Zackel sheep in south Serbia region

Abstract: Sheep production is an example of a sustainable production fully integrated within the local rural development. One of the main threats on the outdoor breeding of sheep is parasitism. Ticks are nuisances and vectors of several diseases agents. The distribution of ticks appears to be changing, with spread to previously unaffected areas. Tick and tick-borne disease control is one of the major components of animal health program protecting livestock in the developing countries, which reflects im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
1
0
Order By: Relevance
“…From the results, we can consider that the tick species distribution differs from area to area and that the three major species present are I. ricinus, D. marginatus, and H. punctata. This is in correlation with available literature data from Serbia (Pavlovic et al 2002;Becskei et al 2015;Milutinovic et al 2008).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…From the results, we can consider that the tick species distribution differs from area to area and that the three major species present are I. ricinus, D. marginatus, and H. punctata. This is in correlation with available literature data from Serbia (Pavlovic et al 2002;Becskei et al 2015;Milutinovic et al 2008).…”
Section: Discussionsupporting
confidence: 91%
“…The dominant tick species collected from sheep, goats, and dogs was Ixodes ricinus followed by occurrence of, for example, Dermacentor marginatus, Dermacentor reticulatus, Rhipicephalus sanguineus, Rhipicephalus bursa, Haemaphysalis punctata, and Haemaphysalis inermis. However, in some geographical areas of Serbia, R. sanguineus was described as the most abundant species on dogs (Milutinović and Radulović 2002;Pavlović et al 2016;Becskei et al 2015;Potkonjak et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison of the obtained results with findings in other regions of Serbia indicated that there is a great similarity in the established tick species. Examination performed in small ruminants in eastern, northeastern, and southern parts of Serbia and the Prizren district (Kosovo) (Milutinović et al, 1987;1997b;1998;Miščević et al, 1990;Pavlović et al, 1995;Petrović et al, 1996;Becskei et al, 2015) pointed to the presence of the same tick species, including Hy. savignyi, Ha.…”
Section: Results and Discusionmentioning
confidence: 99%